PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES TERHADAP HAK-HAK PENGUNGSI: STUDI TERHADAP TERJADINYA PERKAWINAN ANTARA PENGUNGSI DAN WARGA NEGARA INDONESIA - NIM. A1011211206, VIAN AGUSTO AMBARITA (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractMarriage in Indonesia, regulated by Law No. 1 of 1974, is based on religious values. Globalization has enabled mixed marriages between Indonesian citizens and foreign nationals, including refugees. However, Indonesia lacks a legal framework for marriages between Indonesian citizens and refugees, creating issues such as the legal status of children, inheritance rights, and marriage registration. Refugees marrying in Indonesia do not gain citizenship, work rights, or valid civil documents. Since Indonesia has not ratified the 1951 Refugee Convention, refugee matters fall under UNHCR, which provides general protection but lacks specific mechanisms for marital rights. This study examines UNHCR